Contemporary approaches to vocal cord immobility after thyroid surgery - Abduljabbar, Ashraf A.; Almutiri, Manar K.; Alenezi, Ahmad A. Q.; Almesbah, Maryam J.; Alshammari, Duaa F.; Alanazi, Abdulaziz F.; Albishr, Mohammed H.; Aldhafeeri, Reema M.; Alruwaili, Ahmed M.; Aldawas, Ghezlan S. (International Journal Of Community Medicine And Public Health, 2025)
Regardless of the advancements in surgical and management techniques, vocal cord immobility remains the most common complication of thyroid surgery. This can be attributed to the critical and complex location of the recurrent laryngeal nerve (RLN), whose damage contributes to either permanent or temporary vocal cord immobility. However, it can be assessed preoperatively via vocal assessment or laryngeal visualization, monitored perioperatively by intraoperative neuromonitoring, and prevented through identification of both the RLN or the external branch of the superior laryngeal nerve. Post-operative management varies from voice therapy to nerve reinnervation, depending on the degree of severity. The recent employment of artificial intelligence (AI), along with raising patients' awareness and training surgeons, can improve assessment and management approaches. This review aims to explore contemporary approaches for managing vocal cord immobility following thyroid surgery. It also seeks to explain the underlying mechanisms behind vocal cord immobility in order to prompt future research.